Foundation the ways of radio electronic warfare devices development - Kalantaievska, Svitlana; Malyk, Oleg; Tiurnikov, Mykhailo; Zhuk, Pavlo; Shyshatskyi, Andrii; Pikul, Rostislav (Національний технічний університет "Харківський політехнічний інститут", 2019)
The development of radio-electronic warfare systems becomes the most effective, fast-performing, cost-effective, and sometimes the only possible devices, which neutralizes the technical advantage of the opposite side in the information and technology spheres. The main increase in combat potentials in the near future will be possible through the use of intelligent command and control systems for troops and weapons, as well as the use of weaponsthat use unconventional devices of influencing the enemy. The authors of the research found that equipping weapons with the devices and complexes of electronic warfare can repeatedly increase their combat potential and reduce possible losses. In this case, the cost of electronic warfare technology is one percent in relation to the cost of major types of weapons. In the course of the research, the authors used the basic provisions of the theory of electronic warfare, the theory of communication, the theory of signals, and general scientific methods of analysis and synthesis. The authors found that the most important areas of research for the development of electronic warfare systems are: integration of forces and devices of electronic warfare with an intelligence and fire damage in a single information and communication space of all types of armed forces; creation of systems of radio engineering intelligence (passive location) for the reliable disclosure of electronic equipment and high-precision location of objects; Improvement of signal monitoring system in various physical fields. The principal features of the construction of advanced devices and complexes of electronic warfare are: ultra-wide radio engineering part of the equipment (more than 3 octaves); necessity of realization of parallel signal processing of received radio signals in the instant band of frequencies equal to several gigahertz; the maximum increase in the functional density of the apparatus implementation to reduce its mass and overall performance andensure the possibility of its system integration; limit unification of basic digital elements of equipment, which allows to reduce the cost, facilitate the processes of modification and modernization of equipment. Taking into account the above, the direction of further research should be considered the development of methods for increasing the effectiveness of radio-electronic suppression.

Розвиток систем радіоелектронної боротьби стає найбільш ефективним, швидкореалізовуваним, економічно вигідним, а часом і єдино можливим засобом, що нейтралізує технічну перевагу протилежної сторони в інформаційній і технологічній сферах. Основний приріст бойових потенціалів в найближчій перспективі буде можливий за рахунок використання інтелектуальних систем управління військами та зброєю, а також застосування засобів збройної боротьби, які використовують нетрадиційні способи впливу на супротивника. Авторами дослідження встановлено, що оснащення озброєння засобами і комплексами радіоелектронної боротьби здатне багаторазово підвищити їхній бойовий потенціал і знизити можливі втрати. При цьому вартість техніки радіоелектронної боротьби становить одиниці відсотків по відношенню до вартості основних видів озброєння. В ході дослідження авторами були використані основні положення теорії радіоелектронної боротьби, теорії зв’язку, теорії сигналів та загальнонаукові методи аналізу та синтезу. Авторами встановлено, що найважливішими напрямками досліджень для розвитку систем радіоелектронної боротьби є: інтеграція сил і засобів радіоелектронної боротьби із засобами розвідки і вогневого ураження в єдиному інформаційно-комунікаційному просторі всіх видів збройних сил; створення систем радіотехнічної розвідки (пасивної локації) для достовірного розкриття радіоелектронного обладнання і високоточного визначення місця розташування об'єктів; удосконалення системи моніторингу сигналів в різних фізичних полях. Принциповими особливостями побудови перспективних засобів і комплексів радіоелектронної боротьби є: надширокосмугові радіотехнічної частини апаратури (більше 3 октав); необхідність реалізації паралельної сигнальної обробки прийнятих радіотехнічних сигналів в миттєвійсмузі частот, яка дорівнює кільком гігагерц; максимальне збільшення функціональної щільності виконання апаратури для зниження її масогабаритних показників і забезпечення можливості її системної інтеграції; гранична уніфікація базових цифрових елементів апаратури, що дозволяє знизити собівартість, полегшити процеси модифікації і модернізації апаратури. Враховуючи зазначене, напрямком подальших досліджень слід вважати розробку методів підвищення ефективності радіоелектронного подавлення.
Обґрунтування шляхів розвитку засобів радіоелектронної боротьби
Keywords: radio communication systems; radio resources; radio electronic suppression; radio electronicintelligence; система радіозв’язку; радіоресурс; радіоелектронне подавлення; радіоелектронна розвідка